The Role of Youtube Media in Motivation of Early Childhood English Learning - Wijaya, Agung; -, Suryadi (Universitas Trunojoyo Madura, 2024)
This study aims to determine how the use of YouTube videos in teaching English to motivate early childhood to learn the language. This study was conducted at PAUD Al-Hidayah with a qualitative case study approach, with observation, interview, and documentation techniques on four children in group A. The results showed that YouTube significantly increased early childhood motivation in learning English by offering interesting and diverse content, enabling independent learning, and providing real-life examples to support understanding. The main outcomes included increased persistence, increased interest in various topics, preference for independent learning, engagement with non-routine tasks, and increased critical thinking skills. Children aged 4-5 years showed a greater willingness to complete tasks and overcome difficulties by searching for additional resources on YouTube. The variety of topics available on YouTube attracted children's interest, thus encouraging deeper exploration of learning materials. Children preferred to work alone with YouTube because it was more flexible. The variety of content on YouTube helped prevent boredom with routine tasks and kept children engaged. In addition, children were better able to defend their opinions and solve problems using information and examples from YouTube videos. This research supports the integration of modern technology in learning so that it has an impact on children's motivation, abilities and engagement.